Anti-Carbamylated LL37 Antibodies Promote Pathogenic Bone Resorption in Rheumatoid Arthritis - O’Neil, Liam J.; Oliveira, Christopher B.; Sandoval-Heglund, Donavon; Barrera-Vargas, Ana; Merayo-Chalico, Javier; Aguirre-Aguilar, Eduardo; Kaplan, Mariana J.; Carmona-Rivera, Carmelo (Frontiers in Immunology, 2021)
Antibodies against carbamylated proteins (anti-CarP) are associated with poor prognosis and the development of bone erosions in rheumatoid arthritis (RA). RA neutrophils externalize modified autoantigens through the formation of neutrophil extracellular traps (NETs). Increased levels of the cathelicidin LL37 have been documented in the synovium of RA patients, but the cellular source remains unclear. We sought to determine if post-translational modifications of LL37, specifically carbamylation, occur during NET formation, enhance this protein’s autoantigenicity, and contribute to drive bone erosion in the synovial joint. We found significant levels of carLL37 in plasma and synovial fluid from RA patients, compared to healthy controls. RA NETs release carLL37 and fibroblast-like synoviocytes (FLS) internalized NET-bound carLL37 and loaded it into their MHCII compartment. HLA-DRB1*04:01 transgenic mice immunized with FLS containing NETs developed autoantibodies against carLL37. Anti-carLL37 antibodies were present in RA sera and synovial fluid and they correlated with radiologic bone erosion scores of the hands and feet in RA subjects. CarLL37-IgG immune complexes enhanced the ability of monocytes to differentiate into osteoclasts and potentiated osteoclast-mediated extracellular matrix resorption. These results suggest that NETs are a source of carLL37 leading to induction of anti-carbamylated autoantibody responses. Furthermore, carLL37-IgG immune complexes may be implicated in the bone damage characteristic of RA. These results support that dysregulated NET formation has pathogenic roles in RA.